Risk Factors and Clinical Outcomes of Cerebrospinal Fluid Leakage Following Spinal Surgery: Insights from a Single-Center Study - Abdulhadi Y. Algahtani; Khalid Talal Alghamdi; Hamzah A. Alsharif; Ahood Ahmad A Mahjari; Abdulaziz M. Alghamdi; Nawaf A. Bin Khamis; Reuof I. Althegfi; Alwaleed K. Aloufi; Wed Talal Alghamdi; Hussein Matouq Kheshaifat (Journal of Spine Practice)
Background Cerebrospinal fluid (CSF) leak is a known complication of spine surgery, and an effective protocol for prevention, recognition, and treatment of postoperative CSF leak is essential to avoid a cascade of associated adverse outcomes, such as durocutaneous fistula, wound infection, and intracranial hemorrhage. We aim to identify the incidence of CSF leak post spinal surgeries and to obtain the factors that could predict the risks of having a CSF leak following spine surgeries.